Conservation genomics of Pecos pupfish ( Cyprinodon pecosensis ) - Elizabeth P. Dolan; Andrew T. Fields; Megan G. Bean; Robyn R. Doege; Joanna L. Hatt; Kevin W. Conway; David S. Portnoy (Journal of Fish Biology, 2026)
The Pecos pupfish, Cyprinodon pecosensis , is an imperilled freshwater fish found in arid regions of Texas and New Mexico (USA). The species faces multiple challenges to persistence including reductions in suitable habitat, water shortages, as well as hybridization and competition with an introduced congener (sheepshead minnow, C. variegatus ). As part of the current management strategy, refuge populations, seeded with non‐introgressed individuals collected from Texas, are maintained at the Fort Worth Zoo and on private property in West Texas. Therefore, assessments of standing genetic variation within and among wild and refuge populations and levels of admixture in the wild are critical for future conservation and management planning. Fin clips were acquired in 10 locations in the wild, five in Texas, five in New Mexico and from two refuge populations in Texas (one maintained by Fort Worth Zoo and another on a private property in West Texas). In Texas, non‐introgressed C. pecosensis were found in the wild at only one location Upper Salt Creek (USC); all other locations were composed of admixed individuals or non‐introgressed C. variegatus . No admixed individuals were found in New Mexico. Significant genetic heterogeneity was detected between all locations of non‐introgressed C. pecosensis , including the refuge populations, and estimates of divergence between Texas locations (USC and refuge populations) and New Mexico locations were relatively large ( F ST : 0.23–0.32). Estimates of contemporary effective population size for USC and the two refuge populations were less than 50, but greater than 500 for all New Mexico populations. In summation, while New Mexico populations look secure, the data suggest that C. pecosensis in Texas is currently imperilled by the threat of hybridization, as well as potential loss of genetic diversity on contemporary time scales. Deep divergence between Texas (including refuge populations) and New Mexico suggests that further study would be needed prior to any management plans that would involve assisted gene flow between the regions.